Nilai Budaya Dan Tutur Bahasa Dalam Perkembangan Karakter Siswa Di Era Disrupsi - Nur zahirah; Eva Awalia Ramadhani (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Cultural values and language speech are important factors that influence students' attitudes, behavior and self-identity formation. Character education through kind words plays an important role in instilling positive values and supporting a person's character development. Cultural experts believe that language reflects culture and is important for the progress of society. The purpose of this paper is to explain the important role of cultural values and linguistic speech in the development of student character in the era of disruption. The method used in this paper is descriptive with context analysis of cultural values and language speech. The results and conclusions of cultural and linguistic values in the development of student character in the era of disruption are that they are able to form positive student character, cultural and linguistic values in developing student personality are very important in supporting a person's personality development and instilling positive values in society.